2020
DOI: 10.3389/fimmu.2020.02146
|View full text |Cite
|
Sign up to set email alerts
|

Zika Induces Human Placental Damage and Inflammation

Abstract: In Brazil, an epidemic of Zika virus (ZIKV) infections was declared in 2015 that coincided with alarming reports of microcephaly in newborns associated with mother infection. Although the virus has placental tropism, changes in the tissue morphology and immunity of infected patients have not yet been elucidated. Here, we investigated the histopathological and ultrastructural changes along with the immunological profile and the BDNF expression in rare placental material. Tissues were obtained in the 2015–2016 B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 54 publications
5
55
2
3
Order By: Relevance
“…The fact that ZIKV decreased BDNF mRNA expression in first trimester cytrophoblast cells suggests a lower availability of BDNF for fetal nervous system development at this early stage. In line with this finding, a recent retrospective study of placentae from pregnant women infected with ZIKV in the 2015–2016 Brazilian epidemic shows lower BDNF immunostaining intensity and a lower number of BDNF expressing cells in decidua and chorionic villi of ZIKV versus control placenta at term (Rabelo et al, 2020). Interestingly, this difference was even larger in placentae from pregnancies that resulted in babies with birth microcephaly compared to those with normal cranial circumference at birth (Rabelo et al, 2020).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The fact that ZIKV decreased BDNF mRNA expression in first trimester cytrophoblast cells suggests a lower availability of BDNF for fetal nervous system development at this early stage. In line with this finding, a recent retrospective study of placentae from pregnant women infected with ZIKV in the 2015–2016 Brazilian epidemic shows lower BDNF immunostaining intensity and a lower number of BDNF expressing cells in decidua and chorionic villi of ZIKV versus control placenta at term (Rabelo et al, 2020). Interestingly, this difference was even larger in placentae from pregnancies that resulted in babies with birth microcephaly compared to those with normal cranial circumference at birth (Rabelo et al, 2020).…”
Section: Discussionmentioning
confidence: 66%
“…The maternal immune system contributes to limit infections during pregnancy to ensure the survival of the mother and the fetus. In ZIKV infected placenta high CD68+ and TCD8+ cell recruitment as well as higher IFN‐ɣ and TNF‐α expression compared to normal term placenta was reported (Rabelo et al, 2020). However, in contrast to viral infections associated to abortion or preterm delivery, the ZIKV infection does not preclude the progress of pregnancy (Mor et al, 2017; Silasi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CMV may cross the placenta via transcytosis of first-trimester syncytiotrophoblast cells and, in an ex vivo infection decidual organ culture model, HCMV infects invasive cytotrophoblasts, macrophages, and endothelial, decidual and dendritic cells (Weisblum et al, 2011). ZikV has been shown to infect syncytiotrophoblasts, cytotrophoblasts, decidual, and endothelial cells, leading to increased inflammation response, including CD68 and CD8 cell infiltration and cytokines, chemokines and MMP secretion (Rabelo et al, 2020). Additionally, placental cells at birth (mean gestational age 36 weeks) were shown to express AXL, CD209 and TYRO3, which may serve as preferential receptors for the Zika virus entry (Pique-Regi et al, 2020).…”
Section: Congenital Torch Diseasesmentioning
confidence: 99%
“…Histopathological and immunological studies in placentas have shown that infections by ZIKV lead to an increase in important inflammation markers such as TNF, CCL5, and altered vascular permeability such as metalloproteinases [25]. In addition, in vitro experiments demonstrate that trophoblastic cells become progressively more resistant to infection by ZIKV during pregnancy, partly through the secretion of IFNs [26].…”
Section: Introductionmentioning
confidence: 99%